Study of magnitude of knee osteoarthritis among adult population with age 40 years and above in rural area: a cross sectional study - Jadhao, Ashok R.; Dambhare, Punam M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Osteoarthritis (OA) is a degenerative joint disease, which mainly affects the articular cartilage. Worldwide estimates are that 9.6% of men and 18.0% of women aged over 60 years have symptomatic osteoarthritis. It affects the daily physical activities like climbing stairs, squatting etc. Pain is the main symptom. Considering this the study was conducted with the objective to find out the magnitude of knee OA among adult population more than 40 years of age in rural area and to study the association between risk factors and knee OA. Methods: A cross sectional study was conducted in rural health training Centre of study institute. Total 150 patients with knee joint pain were included in the study. Knee OA was diagnosed using American rheumatology criteria (ACR). Analysis was done by using epi info 7. Chi square test and Fischer’s exact test was applied to see the association between risk factors and knee OA. Results: The prevalence of knee OA among study subjects was found to be 34.7%. Study subjects with age >60 years were having prevalence of 32 (43.2%) and this association was statistically significant. The study subjects with history of DM and who are having BMI≥25 were having higher prevalence and the association was statistically significant. Conclusions: The prevalence of knee OA in our study was 34.7%. Factors such as age >60 years, education, occupation, low socioeconomic status, DM, BMI≥25 were having significant association with knee OA.